Perancangan Desain Karakter pada Buku Interaktif Pengenalan Literasi Keuangan untuk Anak Usia Dini - Pramesti, Rizka Sintya; Wulandari, Sri; Setiawan, Bayu (Jurnal Desain Komunikasi Visual Asia, 2024)
The focus of this design is the creation of character designs on interactive financial literacy books media for early childhood. The method used in this design is qualitative and uses qualitative descriptive analysis techniques. Primary data were obtained from interviews, Focus Group Discussions, and observations, while secondary data were obtained from literature and mass media. The design process begins with collecting references, determining concepts, making design alternatives, final designs, and evaluating designs. Verbal and visual concepts refer to the characteristics of the target audience, namely children aged 4-6 years in Indonesia. The drawing style and illustration refers to the book "Sayur Juara" which is used as a study comparator. Characters that have been selected and evaluated, then applied to interactive book media, stickers, and keychains. Introducing financial literacy is important from early childhood. This research is expected to contribute to improving early childhood financial literacy through the development of character designs in interactive books that are interesting and educational.